The Impact of Values-based Leadership on Ethical Loyalty in Saudi Arabian Health Organizations - Yamin, Mohammed Ali Yousef; Mahasneh, Mohamed Sultan (International Review of Management and Marketing, 2018)
The study aims to achieve the following objectives: Know the degree of practice of Values-Based Leadership of Saudi health organizations, know the level of ethical loyalty of Saudi health organizations and know the level of relationship between Values-Based Leadership and ethical loyalty in Saudi health organizations. The results of the test and analysis of the main hypotheses and sub-hypotheses indicated the acceptance and confirmation of all studies hypotheses (main hypotheses and sub-hypotheses). There is also a positive statistical significance relationship between Values-Based Leadership and ethical loyalty. The level of employee’s Values-Based Leadership perception in Saudi health organizations under study is high. The level of employee’s Values-Based Leadership application in Saudi health organizations under study is high. Keywords: Values-Based Leadership, Ethical Loyalty, Health Organizations JEL Classifications: M5, M12